LEGAL CONSEQUENCES OF CHILDREN OUTSIDE OF MARRIAGE AFTER CONSTITUTIONAL COURT DECISION NUMBER 46/PUU-VIII/2010 - Asrul Hamid; Defel Fakhyadi (STIH Putri Maharaja, 2022)
Civil Code, Law Number 1 of 1974 concerning Marriage, and the Compilation of Islamic Law (KHI)is a legal rule that regulates the regulation of children outside of marriage and KHI is specifically for people who are Muslim. Therefore, the Constitutional Court Decision Number 46/PUU-VIII/2010 concerning the position of children out of wedlock is stipulated as a solution so that there is no legal dualism in society. The Constitutional Court's decision was determined when Aisyah Moechtar submitted a judicial review to the Constitution Court about constitutionality of Article 2 paragraph (2) and Article 43 paragraph (1) of Law no. 1 of 1974 concerning Marriage. This happens because of the legal meaning of the phrase